Prognostic relevance of P-cadherin expression in melanocytic skin tumours analysed by high-throughput tissue microarrays. Issue 7 (24th March 2006) - Bauer, R; Wild, P J; Meyer, S; Bataille, F; Pauer, A; Klinkhammer-Schalke, M; Hofstaedter, F; Bosserhoff, A K
Abstract : Aim: To investigate whether protein expression or cellular localisation of P-cadherin is associated with clinicopathological characteristics in benign and malignant melanocytic skin tumours. Experimental design: P-cadherin expression and the Ki-67 labelling index were analysed immunohistochemically by using tissue microarrays (TMAs). Membranous and cytoplasmic expression was scored semiquantitatively (0 to 2+). Results: P-cadherin protein expression of any intensity (1+ to 2+) was detected in the membrane in 41.5% (132/318) and in the cytoplasm in 64.2% (204/318) of patients. In general, P-cadherin expression was significantly reduced in malignant melanomas (p<0.001) and melanoma metastases (p<0.001), compared with benign nevi. Additionally, loss of membranous P-cadherin was associated with Clark level (p = 0.011) and tumour thickness (p<0.001). Interestingly, a significantly lower P-cadherin expression was shown by dermal nevi than by compound and junctional nevi (p = 0.005; p = 0.025). In primary melanomas, a Ki-67 labelling index <5% was not associated with P-cadherin protein expression, suggesting that loss of P-cadherin expression was not associated with proliferation. None of the other clinical and histological factors analysed was significantly related to P-cadherin expression. Low cytoplasmic P-cadherin expression was associated with tumour recurrence (p = 0.03) in all the patients who were analysed. After testing various multivariate Cox regression models, loss of cytoplasmic P-cadherin expression remained a highly significant adverse risk factor for tumour recurrence in patients with tumours <2 mm. Conclusions: Loss of cytoplasmic P-cadherin expression is common in advanced melanomas and can be a prognostic marker of progression in patients with melanoma, most useful in patients with primary tumours <2 mm in thickness.